Brain Neural Underpinnings of Interoception and Decision-Making in Alzheimer's Disease: A Narrative Review - Sun, Weiyi; Ueno, Daisuke; Narumoto, Jin (Frontiers in Neuroscience, 2022)
This study reviews recent literature on interoception directing decision-making in Alzheimer's disease (AD). According to the somatic marker hypothesis, signals from the internal body direct decision-making and involve the ventromedial prefrontal cortex (vmPFC). After reviewing relevant studies, we summarize the brain areas related to interoception and decision-making (e.g., vmPFC, hippocampus, amygdala, hypothalamus, anterior cingulate cortex, and insular cortex) and their roles in and relationships with AD pathology. Moreover, we outline the relationship among interoception, the autonomic nervous system, endocrine system, and AD pathology. We discuss that impaired interoception leads to decreased decision-making ability in people with AD from the perspective of brain neural underpinning. Additionally, we emphasize that anosognosia or reduced self-awareness and metacognition in AD are remarkably congruent with the malfunction of the autonomic nervous system regulating the interoceptive network. Furthermore, we propose that impaired interoception may contribute to a loss in the decision-making ability of patients with AD. However, there still exist empirical challenges in confirming this proposal. First, there has been no standardization for measuring or improving interoception to enhance decision-making ability in patients with AD. Future studies are required to better understand how AD pathology induces impairments in interoception and decision-making.